Dynamic Governance in City Branding : Case Study of Tabebuya in Bojonegoro Regency - Zanuba Safirutol Asca; Ana Kumalasari; Ida Swasanti (Publik : (Jurnal Ilmu Administrasi), 2026)
The “Sakura Bojonegoro” phenomenon represents the organic formation of a city identity through community participation in digital spaces. This study examines how the tabebuya planting program, initially implemented as an environmental policy by local government agencies, evolved into a distinctive city identity through the production and dissemination of visual content on Instagram and TikTok. The research also explores the dynamics of city communication and the government's capacity to respond to rapid social change in the digital era using the perspective of dynamic governance. A qualitative case study with a phenomenological approach was employed to capture the experiences and perceptions of key stakeholders. Data were collected through in-depth interviews, field observations, documentation of social media content, and relevant government documents, and were analysed using NVivo 12 Pro through thematic coding and data triangulation. The findings reveal that the “Sakura Bojonegoro” identity emerged primarily through citizen-generated content and community-driven digital engagement, with minimal direct government intervention. The government remained largely reactive and demonstrated limited readiness to manage rapidly evolving digital narratives, despite showing adaptive institutional responses in environmental policy implementation. This study highlights that community participation and social media have become significant drivers of city branding beyond formal governmental communication. These findings emphasize the importance of adaptive city branding strategies, collaborative governance, and responsive institutional capacities in addressing the emergence of city identities shaped by community initiatives in contemporary digital environments.